Changes in Mid-Depth Water Mass Ventilation in the Japan Sea Deduced From Long-Term Spatiotemporal Variations of Warming Trends - Senjyu, Tomoharu (Frontiers in Marine Science, 2022)
The influence of global warming on mid-depth water mass ventilation in the Japan Sea was investigated using both Argo-based and ship-based hydrographic datasets. The Argo-based dataset of the entire Japan Sea area revealed a warming trend during the past two decades in the upper portion of the Japan Sea Proper Water (UJSPW), which lies at intermediate depths from just under the main thermocline to approximately 1000 m. The warming rates in the southern Japan Sea are generally greater than those in the northern sea by a factor of 2–3. Long-term hydrographic data obtained over the last five decades in the northeast and southeast of the sea revealed that higher warming rates in the southern sea began from 2008, although a significant warming in both northern and southern seas was initiated from the late 1980s. A stagnation in the UJSPW formation from the late 1980s was suggested by a positive shift in the winter sea surface temperature in its formation region and a decreasing trend in dissolved oxygen concentration during the 1990s. In addition, a vertical multi-box model demonstrated that an imbalance between the heating from the upper layer and the cold water supply from its source region induces a warming in the UJSPW. We conclude that a significant change in the mid-depth water mass ventilation occurred in the entire Japan Sea in the late 1980s due to a stagnation in the UJSPW formation. Subsequently, a modest event in the mid-depth water mass ventilation have occurred since 2008. The higher warming rates in the southern sea than those in the northern sea in the event suggest a reduction in cold UJSPW supply to the southern sea from its formation region.